Structural, magnetic and magnetotransport properties of sol-gel synthesized La0.67Ca0.33MnO3: TiO2 nanocomposite - Lau, Lik Nguong; Lim, Kean Pah; Awang Kechik, Mohd Mustafa; Chen, Soo Kien; Ibrahim, Noor Baayah (Scientific.Net, 2020)
. Colossal magnetoresistive (CMR) materials have been widely studied because of their huge potential in spintronic technology. An introduction of secondary phase to the manganite matrix is able to improve the low field magnetoresistance (LFMR). This method is favoured by recent research works as it requires a lower magnetic field compared to intrinsic magnetoresistance. Structural, magnetic properties and magnetotransport properties of polycrystalline (1-x) La0.67Ca0.33MnO3 (LCMO): x TiO2 composites where x = 0.00, 0.05, 0.10, 0.15 and 0.20 were investigated in this work. Polycrystalline La0.67Ca0.33MnO3 (LCMO) was synthesized via sol-gel method and pre-sintered at 800 ºC before appending with nano-sized TiO2. All samples are in LCMO phase having an orthorhombic structure with space group Pnma. The crystal structural parameter was studied by using Rietveld refinement. As the TiO2 content increases, the magnetization is getting higher as observed via vibrating sample magnetometer (VSM) analysis at room temperature. Magnetotransport properties of the pure LCMO sample have been studied from 80 – 220 K. The LFMR is enhanced as the temperature drops. The results have shown LCMO: TiO2 manganite composite is an excellent candidate for future magnetic sensors and memory devices.